Physicochemical, Nutrient, and Heavy Metal Characterization of Wastewater Released from Wachemo University, SNNPR, Ethiopia - M. Z. Haile; F. E. Gedamo (Journal of Applied Sciences and Environmental Management, 2022)
Waste management in higher educational institutions is an existing environmental challenge in Ethiopia. Thus, this study aimed to determine the physicochemical, nutrient, and heavy metals concentration of wastewater generated from Wachemo University, SNNPR, Ethiopia. Three wastewater samples were collected and placed in a refrigerator until sample preparation and analysis. Physicochemical parameters, nutrients, and heavy metals were measured using the Standard Methods of the American Public Health Association. The results of the study were ranged as Temperature (19.00–19.02 oC), TDS (89.9–201 mg/L), E.C (179.9–284 µS/cm), DO (1.5–4.5 mg/L), Turbidity (93.2–513.8 NTU), pH (4.82–7.48), TSS (458.4–143 mg/L), TS (339.7–3889.6 mg/L), BOD (44.9–287.1 mg/L), COD (144.9–869.7 mg/L), phosphate (5.2–13.0 mg/L), sulfate (0.02–280.3 mg/L), nitrate (47.9–54.0 mg/L), NH3–N (0.03–7.39 mg/L). The values of most of the physicochemical parameters, nutrients, and heavy metals are within the permissible limit of FAO and EEPA. However, the concentration of Pb was found to be above the maximum permissible limit set by WHO. Similarly, the values of physicochemical parameters such as BOD, COD, TSS, and E.C were above the acceptable range for wastewater discharged limit set by FAO and EEPA. Thus, the result showed that the wastewater released from Wachamo University pose a risk to the surrounding environment and human health unless a proper waste management system is implemented.